2020
DOI: 10.7717/peerj.9092
|View full text |Cite
|
Sign up to set email alerts
|

Oldest co-occurrence ofVaranusandPythonfrom Africa—first record of squamates from the early Miocene of Moghra Formation, Western Desert, Egypt

Abstract: Lizard and snake remains from the early Miocene (Burdigalian) of the Moghra Formation, Egypt, are described herein. This material comprises the first fossil remains of squamates recovered from the otherwise rich and well known vertebrate assemblage of Moghra. The material pertains to two different genera, the varanid lizard Varanus and the pythonid snake Python and adds to the so far rather poorly known squamate fossil record from Africa. On the basis of the new remains, Moghra marks the oldest so far describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…2003; Georgalis et al . 2016, 2019, 2020 a ). It so remains entirely plausible that pan‐cyclanorbines, which suddenly appear in the African fossil record at that time (Burdigalian), are among the lineages that dispersed from the northern landmasses of Eurasia, a view already suggested by Joyce & Lyson (2010).…”
Section: Discussionmentioning
confidence: 99%
“…2003; Georgalis et al . 2016, 2019, 2020 a ). It so remains entirely plausible that pan‐cyclanorbines, which suddenly appear in the African fossil record at that time (Burdigalian), are among the lineages that dispersed from the northern landmasses of Eurasia, a view already suggested by Joyce & Lyson (2010).…”
Section: Discussionmentioning
confidence: 99%
“…The other lizard group here is represented by a monitor lizard assigned to Varanus. The fossil record of varanids is rather sparse in Asia (Lydekker, 1888;Rage et al, 2001;Malakhov, 2005;Suraprasit et al, 2016;Broin et al, 2020; for an up-to-date table with all early and middle Miocene occurrences of Varanus worldwide, see Georgalis et al, 2020a). The earliest confirmed Asian record of Varanus is reported from the early Miocene of Kazakhstan (Malakhov, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The anterior margin of the neural spine varies in its orientation along with the presacral series from posterodorsally inclined to vertical (figure 1b), and neural spine height probably also varies. Striations are evident on the neural arch (electronic supplementary material, figure S8A) (fibrous striae in [51]). Smith et al [20] suggested that vertebral striae might have arisen on the Varanus stem and have been retained as a plesiomorphy in many crown royalsocietypublishing.org/journal/rstb Phil.…”
Section: (B) Vertebral Columnmentioning
confidence: 99%